2010
DOI: 10.1017/s1751731110000339
|View full text |Cite
|
Sign up to set email alerts
|

Detecting QTL for feed intake traits and other performance traits in growing pigs in a Piétrain–Large White backcross

Abstract: Knowing the large difference in daily feed intake (DFI) between Large White (LW) and Pié train (PI) growing pigs, a backcross (BC) population has been set up to map QTL that could be used in marker assisted selection strategies. LW 3 PI boars were mated with sows from two LW lines to produce 16 sire families. A total of 717 BC progeny were fed ad libitum from 30 to 108 kg BW using single-place electronic feeders. A genome scan was conducted using genotypes for the halothane gene and 118 microsatellite markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
(55 reference statements)
2
16
1
1
Order By: Relevance
“…The same QTL for FCR using the same experimental population as in the current study was reported in a previous study where the authors also suggested the segregation of the IGF2 allele as a candidate gene for this QTL, which is associated with fatness and growth [8]. In addition, this region has been shown in the literature to be associated with ADG, ADFI, body weight, ultrasonic backfat and FCR [7,8,19,23-25]. The QTL for REI, FCR, NEWG, TNE and APD reported in the current study had an additive mode of inheritance compared to the QTL for IGF2, which showed genomic imprinting, indicating that, besides the QTL for IGF2, there might be an additional QTL for APD on SSC2 around this location causing the improvement in efficiency of protein deposition.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The same QTL for FCR using the same experimental population as in the current study was reported in a previous study where the authors also suggested the segregation of the IGF2 allele as a candidate gene for this QTL, which is associated with fatness and growth [8]. In addition, this region has been shown in the literature to be associated with ADG, ADFI, body weight, ultrasonic backfat and FCR [7,8,19,23-25]. The QTL for REI, FCR, NEWG, TNE and APD reported in the current study had an additive mode of inheritance compared to the QTL for IGF2, which showed genomic imprinting, indicating that, besides the QTL for IGF2, there might be an additional QTL for APD on SSC2 around this location causing the improvement in efficiency of protein deposition.…”
Section: Discussionsupporting
confidence: 79%
“…These QTL for ADFI at 60 to 90 kg, and 90 to 120 kg growth stages has been reported by Mohrmann et al [10] using the same experimental population as in the current study. Gilbert et al [7] reported a QTL for FCR in this region for Pietrain-Large White backcross. In addition, at 90 to 120 kg of growth, on SSC6, the additive effect QTL associated with reduction of ADNE indicates that the allele originating from the Pietrain grandpaternal breed is associated with a reduction in nitrogen excretions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have been conducted to identify QTLs and candidate genes putatively influencing RFI in pigs. Using a Piétrain–Large White backcross population, Gilbert et al (2010) identified QTLs on pig chromosomes (SSC) 5 and 9 for RFI in growing pigs. In Yorkshire pigs, a GWA study revealed several significant SNPs on SSC 2, 3, 5, 7, 8, 9, 14, and 15 influencing RFI (Onteru et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in plant breeding to precisely improve the target trait by transferring the associated gene(s) from the donor parent to the recurrent parent, to control hybrid populations, and to overcome the barriers of distant crosses, and so on. Backcrossing is also a very useful design for dissecting the genetic mechanism of quantitative traits, and has been used in mapping QTLs for complex traits in crops and animals [28,29]. Advanced backcrossing has been used for fine mapping of QTLs [30,31].…”
Section: Discussionmentioning
confidence: 99%